2007
DOI: 10.1111/j.1600-0560.2007.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐pustular palmoplantar psoriasis: is histologic differentiation from eczematous dermatitis possible?

Abstract: The differential diagnosis of psoriasis affecting palmoplantar skin might be troublesome because of the anatomic properties of this region. Both palmoplantar psoriasis and eczematous dermatitis of this skin area share similar histologic features. The punch biopsies from 17 patients with psoriasis and 25 with eczematous dermatitis were evaluated, blind to the clinical diagnosis. Vertically situated multiple foci of parakeratosis, alternating with orthokeratosis, were the only statistically significant feature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 3 publications
5
43
1
1
Order By: Relevance
“…The histological parameters were established according to the features that were considered helpful in the diagnosis of psoriasis in literature 4 . These parameters had been also used to differentiate non‐pustular palmoplantar psoriasis from eczematous dermatitis 5 …”
Section: Methodsmentioning
confidence: 99%
“…The histological parameters were established according to the features that were considered helpful in the diagnosis of psoriasis in literature 4 . These parameters had been also used to differentiate non‐pustular palmoplantar psoriasis from eczematous dermatitis 5 …”
Section: Methodsmentioning
confidence: 99%
“…Exemplarily, difficulties occur when distinguishing seborrheic scalp dermatitis from scalp psoriasis due to psoriasiform hyperplasia and neutrophil infiltration in seborrheic dermatitis or when clarifying the diagnosis of palmoplantar psoriasis and hand eczema. In the latter case, due to the anatomic properties of the palm, histology often provides merely diagnostic clues [2,3].…”
mentioning
confidence: 99%
“…It is shown that the most important histopathological distinction between these two diseases is multi focal parakeratosis (5) . In the other study, while it is emphasized even the histopathological differentiation of psoriasis and eczema is very difficult, it has been suggested that these two diseases have similar clinical, histologic, biologic and therapeutic responses and there is an overlap condition (6) .…”
Section: Discussionmentioning
confidence: 99%